Arabic Online Learning At The Islamic Elementary School Level - Anwar Sidik*; Sa'idatul Abidah (The Progress: Journal of Language and Ethnicity, 2022)
This study reveals the supporting and inhibiting factors experienced by educators, students, as well as parents when carrying out the online education process for Arabic subjects at Madrasah Ibtida'iyyah elementary schools. Field data in the form of interviews and observations will be analyzed in qualitative form and described descriptively. After the researchers analyzed this research, it showed that the online learning process at MI Miftakhul Khoirot caused new problems which were influenced by several factors, both supporting and inhibiting factors. As a result, teachers, students, and parents should be able to adapt to using the online learning system to keep it running smoothly and efficiently.